2019
DOI: 10.1002/jcp.29303
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 reduces mitochondrial damage to photoreceptors of primary retinal cells exposed to high glucose

Abstract: No study has investigated the interaction of Resolvin D1 (RvD1) with mitochondrial damage of retinal cells caused by diabetes. This study aims to investigate the effects of RvD1 (50 nM) on morphological and biochemical indicators of mitochondrial damage in primary retinal cells exposed to 30 mM D-glucose high glucose (HG). HG-cells exhibited photoreceptor damage characterized by short and small mitochondria with prevalent mitochondrial disruption, fragmentation, and aggregation. The cells had low mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…It is reported that these differential genes play an important role in the process of mitochondrial damage. [34][35][36][37][38][39] For example, the expression of ndufb6 and ndufs3 increased after AF-HF001 treatment, which increased myocardial contractility and improved oxidative damage. 38 Overexpression of Uqcrh can improve mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that these differential genes play an important role in the process of mitochondrial damage. [34][35][36][37][38][39] For example, the expression of ndufb6 and ndufs3 increased after AF-HF001 treatment, which increased myocardial contractility and improved oxidative damage. 38 Overexpression of Uqcrh can improve mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mitochondrial damage determines myocardial damage during IR and subsequent remodeling [34][35][36]. RvD1 has already been proven to reduce reactive oxygen species levels, improve mitochondrial morphology and function, promote mitochondrial DNA repair in primary retinal cells with diabetic retinopathy [37]. In diabetes, high blood glucose and free fatty acids induce ECs mitochondrial ssion, with high levels of reactive oxygen species (ROS), leading to blunted cell growth and altered cell-adhesion molecule expression on the cell surface [38].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with sh oil for MCMV infection promoted mitochondrial biosynthesis in the liver cells of male C57BL/6 mice [38]. Both RvD1 and MCTR1 have been reported to improve mitochondrial biogenesis and function induced by multiple adverse factors, such as in ammation or high sugar [39][40][41].…”
Section: Discussionmentioning
confidence: 99%